Augmented Reality Evidence: A Study of The Validity of Virtual Evidence in Islamic Courts - Luthfi, Fuad (JURNAL AKTA, 2025)
his study examines the validity of Augmented Reality (AR) Evidence as a new form of evidence in the Islamic judicial system. The development of digital technology, particularly AR and Virtual Reality (VR), has presented new challenges and opportunities in the practice of evidence in court. The main objective of this study is to analyze whether AR-based virtual reconstructions can be recognized as valid evidence under Islamic law, and how their application is in line with the principles of fiqh al qadha and maqashid al syariah. The method used is normative-legal research (doctrinal legal research) with three main approaches: (1) the fiqh al qadha approach to examine the procedural norms of Islamic courts; (2) the maqashid al syariah approach with a focus on justice, protection of rights, and prevention of harm; and (3) a comparative approach, namely comparing modern regulations on e-litigation and electronic evidence with the perspective of classical Islamic law. Primary sources include the Qur'an, Hadith, and the works of classical scholars such as al Mawardi, Ibn al Qayyim, and al Sarakhsi, in addition to contemporary religious court decisions. Secondary sources include Islamic law journals, AR/VR literature, and regulations related to electronic evidence. The results of the study show that AR Evidence cannot be positioned as bayyinah (primary evidence), but rather as qarinah (supporting evidence) that strengthens other evidence. The acceptance of AR Evidence requires strict regulations and authentication mechanisms to prevent technological manipulation, including the potential for deepfakes. Furthermore, placing AR Evidence within the framework of maqashid al syariah will ensure that its use supports justice and protects the rights of the parties. The contribution of this research lies in the novelty of the idea of positioning AR technology in the discourse of Islamic judicial evidence, thus opening up space for the development of fiqh al qadha that is responsive to digital disruption.